2017
DOI: 10.3389/fendo.2017.00092
|View full text |Cite
|
Sign up to set email alerts
|

Hashimoto’s Thyroiditis and Autoimmune Gastritis

Abstract: The term “thyrogastric syndrome” defines the association between autoimmune thyroid disease and chronic autoimmune gastritis (CAG), and it was first described in the early 1960s. More recently, this association has been included in polyglandular autoimmune syndrome type IIIb, in which autoimmune thyroiditis represents the pivotal disorder. Hashimoto’s thyroiditis (HT) is the most frequent autoimmune disease, and it has been reported to be associated with gastric disorders in 10–40% of patients while about 40% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 49 publications
0
54
0
6
Order By: Relevance
“…Other authors have suggested an increased risk of additional diseases in Hashimoto's disease patients e.g. iron deficiency anaemia, pernicious anaemia [12], ischemic heart disease [13], cardiovascular disorders, atherosclerosis [14], idiopathic urticaria [20], thyroid cancer, colon cancer [21]. The most common symptoms in the respondents prior to the diagnosis of Hashimoto's thyroiditis included fatigue/weakness/drowsiness (n=122, 87.7%), difficulty in concentration/weak memory (n=88, 63.3%), increased body weight (n=85, 61.1%), mood swings/depression (n=82, 58.9%), skin lesions (n=80, 57.55%), and nervousness (n=80, 57.55%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have suggested an increased risk of additional diseases in Hashimoto's disease patients e.g. iron deficiency anaemia, pernicious anaemia [12], ischemic heart disease [13], cardiovascular disorders, atherosclerosis [14], idiopathic urticaria [20], thyroid cancer, colon cancer [21]. The most common symptoms in the respondents prior to the diagnosis of Hashimoto's thyroiditis included fatigue/weakness/drowsiness (n=122, 87.7%), difficulty in concentration/weak memory (n=88, 63.3%), increased body weight (n=85, 61.1%), mood swings/depression (n=82, 58.9%), skin lesions (n=80, 57.55%), and nervousness (n=80, 57.55%).…”
Section: Resultsmentioning
confidence: 99%
“…The immune system in Hashimoto's disease patients is dysregulated; hence, they often develop other autoimmune diseases, e.g. vitiligo, rheumatoid arthritis, celiac disease, type 1 diabetes [10,11], anaemia [12], ischemic heart disease, or atherosclerosis [13,14]. The aetiology of the disease is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, the exact mechanism linking thyroid and gastric cell dysfunction is still unknown. Here we describe an interesting case that serves as a reminder of this heterogeneous condition and exemplifies the usual presentation of this rare syndrome [3].…”
Section: Introductionmentioning
confidence: 83%
“…PAS type IIIB, also known as thyrogastric syndrome, was first described in the early 1960s and refers to the presence of thyroid autoantibodies in patients with pernicious anemia [3]. The follicular thyroid cells and the parietal cells both have endodermal origins, are both polarized, are both characterized by the presence of apical microvilli housing enzymatic activities, and both transport iodine across the cell membrane through Na +/I-symporters.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with diagnosed autoimmune disease, changes in the functioning of other organs/systems often develop with time (or simultaneously). Probably it is the result of general immune disturbances accompanying these diseases as well as cross reactions that show many types of antibodies [13,[16][17][18][19][20][21][22][23][24][25]. Understanding the pathomechanism of the above phenomenon and expanding the diagnosis to detect the dysfunction of the other organ even before a clear clinical manifestation of the primary disease is justified, especially because starting the primary disease treatment can make this diagnosis more difficult.…”
Section: Introductionmentioning
confidence: 99%